On the Foaming Kinetics of Gas Well Deliquification Process - Deng, Qiang; Yan, Yong-Li (Asian Journal of Chemistry, 2012)
A kinetic model was proposed to describe the formation behaviour of foams utilized in gas well deliquification processes. The foaming profiles themselves were determined by reading the foam volume as a function of time in the presence of various concentrations of a-olefin sulfonate (AOS), under the conditions of different temperatures. Effect of the surfactant concentration, blowing rate of nitrogen gas and system temperature on the formation of foams was discussed. The formation behaviour was fitted by the empirical equation dV/dt = kwaub. These parameters could be calculated from the experimental data. This kinetic model was tested successfully with the use of the Arrhenius equation, which relates in its logarithmic form of the kinetic constant (ln k) linearly to the reciprocal of the absolute temperature (1/T).